spanish Werewolf motives for reading literature - Abreu Cornelio, Agustin (Emerging Trends in Education, 2023)
El secreto del hombre-lobo addresses the scarce discussion about teaching literature despite the wide emphasis on improving reading comprehension. It is not a product of meticulous academic research based on quantitative or qualitative methodologies. It is a work that emerges at the crossing concerns of parents, literature teachers, regular readers and writers, since José Castillo Baeza is all of these. After publishing the novels Hojas recicladas (2005) and Garabato (2014), and the book of short stories A la espera (2008), Castillo Baeza brought together twenty-four essays previously published in newspapers and journals. The first of the three chapters focuses on the bonds between literature and education; the second one includes interpretive essays about books and movies; while, in the last one, reality is analyzed with tools acquired through reading literature.